2018
DOI: 10.13005/ojc/340134
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition Effect of 2,2’-Bipyridyl on the Corrosion of Austenitic Stainless Steel in 0.5M H2 SO4

Abstract: The corrosion inhibition of AISI309 austenitic stainless steel by 2,2'-Bipyridyl in 0.5M H 2 SO 4 at 298K was studied using the mass loss' method, the potentiodynamic polarization (Tafel), the linear polarization (LRP) and the electrochemical impedance spectroscopy (EIS). The results showed a mixed inhibition mode and an increase in the charge transfer resistance, due to inhibitor molecules' adsorption at steel surface. This latter obeys to Langmuir isotherm. The observation by scanning electron microscopy (SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…It was reported by previous studies that corrosion of materials is affected by chromium content. These studies have shown that Chromium-rich materials exhibit better corrosion behaviour [50,51]. In high chromium cast iron, the chromium is bonded with carbon to form M7C3 type carbides.…”
Section: Electrochemical Behaviourmentioning
confidence: 99%
“…It was reported by previous studies that corrosion of materials is affected by chromium content. These studies have shown that Chromium-rich materials exhibit better corrosion behaviour [50,51]. In high chromium cast iron, the chromium is bonded with carbon to form M7C3 type carbides.…”
Section: Electrochemical Behaviourmentioning
confidence: 99%
“…We notice that the two polarization curves show a substantially identical behavior. They illustrate a cathodic and anodic domains corresponding respectively to a reduction and oxidation reactions [25,26] with the presence of the passive region in the anodic domain. The hardening treatment causes a shift in the corrosion potential of AISI L6 steel to positive values from -644 to -622 mV/SCE accompanied by a decrease in the corrosion current density from 0.095 to 0.087 µA/cm2.…”
Section: Electrochemical Behaviormentioning
confidence: 99%